Greco-Eastern religious fund as the founder of education in Bukovina - Mykhailo Gnydka (Українське Pелігієзнавство, 2014)
Considering the period of the fund's activities, namely the end of the 18th and the beginning of the 20th century, one should pay attention to the state of education of Bukovina before the foundation, in particular, in the pre-Austrian period. The situation with education here was not the best, but on the contrary - she was in an abandoned state. At that time the church was engaged in school, and therefore the focus was on religious education. The first schools in the country were founded at the Putna monastery and in the region of Suceava and Radovtsy. If the boyars wanted to give their sons a higher education, they were forced to send them to Ukrainian schools in Lviv or Kiev, and whether in the capital of Western European countries - Vienna or Paris. It follows that the majority of the population, which remained outside the spiritual state or origin not from the boyars, remained illiterate, but in decades and was completely ignorant. This situation with education in the region was until the annexation of Bukovina by the Austrian Empire in 1774